2016
DOI: 10.1021/acs.jpca.6b09797
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Nonlinear Optical Properties of Carboranylated Square-Planar Pt(II) Zwitterionic Complexes: One-/Two-Dimensional Difference and Substituent Effect

Abstract: Zwitterionic complexes have been the subject of great interest in the past several decades due to their multifunctional application in supramolecular chemistry. Herein, a series of internally stable charge-compensated carboranylated square-planar Pt(II) zwitterionic complexes have been explored by density functional theory aim to assessing their structures, the first hyperpolarizabilities, first hyperpolarizability densities, and electronic absorption spectra. It is found that the first hyperpolarizabilities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 82 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Overall, the topological switches of octaphyrins trigger dramatic changes in β zzz (∞), which is much greater than their effect on molecular polarizability. What is particularly noteworthy is that the calculated first hyperpolarizability components β zzz (∞) of Mobius-type [32]octaphyrins(1.0.1.0.1.0.1.0) are even higher than that of the carboranylate square-planar Pt(II) zwitterionic complexes 53 and can be comparable with that of the traditional D−π−A chromophores. 54 This fact indicates that the nonlinearity of the studied systems can be tuned in a wide range to meet the requirements of practical application.…”
Section: Results and Discussion I T I S I M P O R T A N T T O P O I N...mentioning
confidence: 97%
“…Overall, the topological switches of octaphyrins trigger dramatic changes in β zzz (∞), which is much greater than their effect on molecular polarizability. What is particularly noteworthy is that the calculated first hyperpolarizability components β zzz (∞) of Mobius-type [32]octaphyrins(1.0.1.0.1.0.1.0) are even higher than that of the carboranylate square-planar Pt(II) zwitterionic complexes 53 and can be comparable with that of the traditional D−π−A chromophores. 54 This fact indicates that the nonlinearity of the studied systems can be tuned in a wide range to meet the requirements of practical application.…”
Section: Results and Discussion I T I S I M P O R T A N T T O P O I N...mentioning
confidence: 97%
“…Carboranes [CB 11 H 12 ] − and C 2 B 10 H 12 , in which one or two vertices in boron icosahedron are replaced by a carbon unit, are a fascinating family of compounds with exceptional chemical and thermal robustness, unique geometry, rigidity, and synthetic versatility [1]. Selective chemical substitution of hydrogen atoms at carbon or boron atoms in these clusters allows for their use as rigid, three dimensional scaffolds upon which to construct new materials, such as liquid crystals [2][3][4][5], nonlinear optical materials [6][7][8][9], carboranebased anticrowns [10], and even in drug design [11,12]. As rigid molecules of fixed length, carboranes can be used as building blocks ("molecular tinkertoys") [13][14][15][16][17][18] for supramolecular assemblies, such as porous coordination polymers or metal-organic frameworks (MOFs) [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For nearly almost half a century, interests in the chemistry of carboranes and metallacarboranes have been extended to the electrical, magnetic, and NLO properties since they were first discovered and characterized in the 1960s. However, compared to the most well-known and extensively studied example of closo-carboranes like icosahedral ortho- , meta- , and para- C 2 B 10 H 12 , systematic studies of nido-carborane (nest-like) such as [C 2 B 4 H 6 ] 2– or [C 2 B 9 H 11 ] 2– and arachno-carborane (cobweb-like) such as [C 2 B 3 H 5 ] 4– have remained exceedingly rare up to now. , In the preceding publications, Grimes and co-workers have described the synthesis of several families of metallacarborane sandwich complexes like cobaltacarboranes and ferracarboranes, which covalently bound aryl- and alkynyl-linked polynuclear metallacarboranes that incorporate MC 2 B 4 clusters (Scheme ). Meanwhile, in these metallacarborane complexes, it has been demonstrated that the pyramidal Et 2 C 2 B 4 H 4 2– carborane ligand has strong electron-donating properties.…”
Section: Introductionmentioning
confidence: 99%